The integrated study of the effects of infographic design on waste separation behavior and the behavioral outcome implementation on waste composting - Leeabai, Nattapon; Siripaiboon, Chootrakul; Taweengern, Kor; Buttanoo, Chanatip; Sujirapatpong, Wasin; Yimyam, Disorn; Takahashi, Fumitake; Areeprasert, Chinnathan (Waste Management, 2023)
[Display omitted] •The designed infographics induce waste separation intention.•Larger text size on the infographic is more preferred.•Bone/shell wastes are high perceptive classification as compostable.•The germination index of the compost decreased with the increase of contamination.•The calcium content in the compost increased with the increase of contamination. This study revealed the effects of designed infographics for waste separation and the implementation of behavioral outcomes using surveys and lab-scale experiments. The designed infographics improved the waste separation behaviors of the respondents in term of subject norm, perceived behavioral control, and intention. These influential factors were increased by 5.84 to 20.5%. The effects of design elements including waste separation mascots, the knowledge of waste separation, and the knowledge of waste management were dependent on the ratio of graphics and messages. Therefore, the careful attention on design elements of the infographic had to be noted. According to survey results, animal bone and shell wastes were the highest miss-sorting waste for the compostable waste bin. Although the contamination rate of these wastes did not significantly affect the decomposition of organic waste in the composting process, the quality of the product was degraded in term of toxicity. The germination index was decreased by 66.0% under a 10% contaminated condition. In contrast, the increased the total Ca of compost was increased. Furthermore, the other chemical components of final composts were similar under various conditions. It could be concluded that the mixture of animal bone and shell in compostable waste is acceptable for the purpose of waste reduction. However, the contamination rate of inappropriate wastes in the compostable waste bin should be minimized to enable effective waste composting. The significant findings of this study will be able to apply to the design of waste separation at the source and the plan of waste management.